Assessment of Effectiveness of Cryopreserved Multipotent Mesenchymal Stromal Cells from Adipose Tissue in Adjuvant Arthritis Treatment - Vvedenskyy , Dmytro; Volkova , Nataliia; Goltsev , Anatoliy (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 292